Calibration method of vision measurement system for ceramic billet grinding robot. Issue 7 (23rd April 2019) - Diao, Shipu; Chen, Xindu; Wu, Lei
Abstract : The accuracy of the grinding robot's vision measurement system directly affects the machining accuracy. This study proposes a calibration method of the visual measurement system installed on the fourth joint of the ceramic billet grinding robot. This calibration method includes two steps: preliminary calibration and precise calibration. Preliminary calibration is to fit the transformation matrix between robot frame and vision measurement system frame by describing the same workpiece in different frames. In the precise calibration, the visual measurement error compensation model includes the kinematics error of the robot and the preliminary calibration error. The experimental results show that the calibration method proposed in this study can calibrate the three‐dimensional (3D) vision measurement system of the robot with high precision. Besides, the repeated measurements of the same spatial point by the vision measurement system in different poses indicate that the calibrated visual system has good detection stability. The calibration method only needs to use the laser tracker and 3D scanner to collect the coordinates of the space point to complete the calibration process, which is suitable for the industrial site.